2018
DOI: 10.1111/nbu.12321
|View full text |Cite
|
Sign up to set email alerts
|

3‐carboxy‐4‐methyl‐5‐propyl‐2‐furanpropanoic acid (CMPF): A metabolite identified after consumption of fish oil and fish

Abstract: 3‐carboxy‐4‐methyl‐5‐propyl‐2‐furanpropanoic acid (CMPF) is a known metabolite of furan fatty acids and was first referred to as a urofuran fatty acid, as it was found in urine of humans and other species after consumption of furan fatty acids or foods containing furan fatty acids. More recently, CMPF has been identified as a highly prominent metabolite following the consumption of fish oil, fish oil fractions and diets rich in fish, and can be regarded as biomarker of oil‐rich fish or fish oil intakes. As fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…The richest dietary sources of furan fatty acids and their metabolite CMPF are fish and fish oils. Moreover, several studies have identified plasma CMPF as a biomarker for fish consumption ( 23 ). The main dietary source of TMAO, on the contrary, is animal food, including red meat and egg rich in choline and carnitine, but also fish.…”
Section: Introductionmentioning
confidence: 99%
“…The richest dietary sources of furan fatty acids and their metabolite CMPF are fish and fish oils. Moreover, several studies have identified plasma CMPF as a biomarker for fish consumption ( 23 ). The main dietary source of TMAO, on the contrary, is animal food, including red meat and egg rich in choline and carnitine, but also fish.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals this metabolite is likely produced from the degradation of the methyl group in the β1 position by ω-oxidation, originating only from furan fatty acids with propyl in the position α2. This reaction is likely to occur in the liver, but perhaps it can also be carried out by the microbiota in the large intestine and suffers interference from the circadian cycle (Sinclair et al, 2018;Xu et al, 2017). Moreover, the detection of nonconjugated compounds in urine was previously reported as a result of active tubular secretion in the kidneys (Tsutsumi et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Widespread in food, F-acids are found in vegetables, fruits, seed oil, milk fat, butter, fish, and fish oil. In plants, F-acids are secondary metabolites produced in the process of defense against oxidative stress (Hanhineva et al, 2015;Sinclair et al, 2018). Mammals cannot synthesize these compounds, so they are introduced into the human body through food and the excretion of their metabolites can be observed in urine and blood.…”
Section: Resultsmentioning
confidence: 99%
“…To verify the accuracy of UPLC-Q-TOF-MS E analysis methods in identifying metabolites, we first annotated serum DHA, EPA and their significant metabolite, 3-carboxy-4methyl-5-propyl-2-furanpropanoic acid (CMPF), 32,33 and further analysed the relative abundances of serum DHA, EPA and CMPF at the baseline and at the endpoint of the trial. As shown in Fig.…”
Section: Exploration Of Potential Differences In Metabolite Profiles ...mentioning
confidence: 99%